PEMANFAATAN SUMBER BELAJAR DENGAN LIMBAH KARDUS UNTUK MENGEMBANGKAN KONSEP MATEMATIKA PERMULAAN ANAK USIA 5-6 TAHUN (STUDI EKSPERIMEN DI TK TAMAN INDRIA SEMARANG) - Hayuningtyas, Hesti (BELIA: Early Childhood Education Papers, 2014)
Learning process is closely related to interaction among the teacher, the students, and the source of the learning itself. The source of learning is frequently used by the teacher to support the learning activity. Introduction of basic mathematics concept should be given from an early age. One of the way to develop basic mathematics to children is by learning process at school. Learning process which is held in communities is the effective way to introduce basic mathematics concept. According to Sudjana and Rivai (Prastowo, 2012:2), source of learning is the energy that can be used to give simplicity to someone in his or her learning.The aim of this research is to know the usage of cardboard waste as the learning source in developing basic concept of mathematics. This research is kind of an experiment pretest-posttest control group design. The sampling process uses simple random sampling technic, as the samples are Taman Indria kindergarten as the experiment group and PGRI 02 Mlatiharjo 1 kindergarten as the control group. The t paired test between pretest and posttest in experiment group has obtained significant score (2-tailed) < 0,05 is that 0,000 that means there is a significant difference , however the t paired test between pretest and posttest in control group has obtained significant score (2-tailed) < 0,05 is that 0,018 that means there is no significant enhancement. The result test of t paired posttest in control and experiment group is that there are significant difference because it has significant score (2-tailed) < 0,05 is that 0,000 that means there is significant difference There is a distinction in basic concept of mathematics in children of experiment group before and after they are given the cardboard waste as the learning source. It is known that there is a difference comprehension of basic concept of mathematics between the children of experiment and control group after the treatment. Therefore, cardboard waste as the learning source is effective to develop basic concept of mathematics in 5-6 years old children. School as the education facilities should give another learning source or another literature to develop the basic concept of mathematics in order to children can get better basic concept of mathematics and they will have good understanding in it.